Lateral Extra-articular Tenodesis Contributes Little to Change In Vivo Kinematics After Anterior Cruciate Ligament Reconstruction: A Randomized Controlled Trial. Issue 7 (June 2021) - Chiba, Daisuke; Gale, Tom; Nishida, Kyohei; Suntaxi, Felipe; Lesniak, Bryson P.; Fu, Freddie H.; Anderst, William; Musahl, Volker
Background: Lateral extra-articular tenodesis (LET) in combination with anterior cruciate ligament (ACL) reconstruction (ACLR) has been proposed to improve residual rotatory knee instability in patients having ACL deficiency. Purpose/Hypothesis: The purpose was to compare the effects of isolated ACLR (iACLR) versus LET in combination with ACLR (ACLR+LET) on in vivo kinematics during downhill running. It was hypothesized that ACLR+LET would reduce the internal rotation of the reconstructed knee in comparison with iACLR. Study Design: Controlled laboratory study. Methods: A total of 18 patients with ACL deficiency were included. All participants were randomly assigned to receive ACLR+ LET or iACLR during surgery. Six months and 12 months after surgery, knee joint motion during downhill running was measured using dynamic biplane radiography and a validated registration process that matched patient-specific 3-dimensional bone models to synchronized biplane radiographs. Anterior tibial translation (ATT; positive value means "anterior translation") and tibial rotation (TR) relative to the femur were calculated for both knees. The side-to-side differences (SSDs) in kinematics were also calculated (operated knee–contralateral healthy knee). The SSD value was compared between ACLR+LET and iACLR groups using a Mann-Whitney U test. Results: At 6 months after surgery, the SSD of ATT in patients who had undergone ACLR+LET (–1.9 ± 2.0 mm) was significantly greater than that in patients who had undergone iACLR (0.9 ± 2.3 mm) at 0% of the gait cycle (foot strike) ( P = .031). There was no difference in ATT 12 months after surgery. Regarding TR, there were no differences between ACLR+LET and iACLR at either 6 months ( P value range, .161-.605) or 12 months ( P value range, .083-.279) after surgery. Conclusion: LET in combination with ACLR significantly reduced ATT at the instant of foot strike during downhill running at 6 months after surgery. However, this effect was not significant at 12 months after surgery. The addition of LET to ACLR had no effect on TR at both 6 and 12 months after surgery. Clinical Relevance: LET in combination with ACLR may stabilize sagittal knee motion during downhill running in the early postoperation phase, but according to this study, it has no effect on 12-month in vivo kinematics. Registration: NCT02913404 (ClinicalTrials.gov identifier)